(untitled) (Eurasian Scientific Herald, 2022)
This article is devoted to the study of phraseological units in English and Uzbek languages that are not related to each other. Phraseological units are important tools for creating imagery, expressiveness, and emotionality, and they serve to increase the expressive effectiveness of artistic publicist texts. Phraseological units fit the spirit of the period because of their conciseness, semantic weight, and impact. This, in turn, proves once again the relevance and importance of phraseological research at the present time. The collected materials and their analysis can be used in the process of literary translation, as well as in lecturing on the course of English lexicology, practical training and compiling dictionaries. In addition, based on the results of this analysis, words and phrases from other lexical-semantic groups can be studied both functionally and semantically. A comparative study of the phraseology of different languages provides a deeper understanding of the structure of both languages, which serves to enrich the knowledge of the culture, literature, history, and customs of the people who speak these languages